Pengaruh Kualitas Pelayanan Islam terhadap Loyalitas Pelanggan dengan Mediasi Kesenangan Pelanggan pada Penginapan Syariah di Mojokerto - Fachreza Eka Kurnia; Achsania Hendratmi; Saiful Anam; Muhammad Nur Miftakhul Ivanda (Universitas Jember, 2023)
This study's objective is to investigate the relationship between the quality of sharia-compliant customer service and the degree of customer loyalty, with the satisfaction of customers serving as a moderating variable. The participants in this study were customers who had previously utilised the services provided by sharia inns in Mojokerto. The research was carried out in a number of sharia inns in Mojokerto. The data analysis technique uses Regression Path Analysis. The empirical research results prove that service quality influences customer loyalty and customer satisfaction, and customer satisfaction influences customer loyalty. The results of the study also found that customer satisfaction mediates the effect of service quality on customer loyalty. In an increasingly competitive business era, service quality and customer satisfaction play a very important role for a company's success. Good service quality and customer delight can help build long-term relationships with customers. When customers are satisfied with the services provided, they tend to remain loyal and not switch to competitors. Keywords: Customer Loyalty, Customer Satisfaction, Islam Service Quality